Cultural brokers at Mediterranean courts in the Middle Ages: papers ... presented at a Conference on "Cultural Brokers Between Religions: Border-Crossers and Experts at Mediterranean Courts" held in Bochum on the 28th to 30th of October 2010 - Höh, Marc von der; Jaspert, Nikolas; Oesterle-El Nabbout, Jenny Rahel (Mittelmeerstudien, 2013)
Intro -- CULTURAL BROKERS AT MEDITERRANEAN COURTS IN THE MIDDLE AGES -- CONTENTS -- Preface -- Courts, Brokers and Brokerage in the Medieval Mediterranean -- Jews at the Mongol Court in Iran: Cultural Brokers or Minor Actors in a Cultural Boom? -- The Emergence of an Islamic Culture in Early Abbasid Iraq: The Role of non-Arab Contributions -- Missionaries as Cultural Brokers at the Fatimid Court in Cairo -- Trujamanes and Scribes: Interpreting Mediation in Iberian Royal Courts -- Love Without Borders: Jewish and Muslim Paramours in 13th and 14th Century Castile -- Mendicants, Jews and Muslims at Court in the Crown of Aragon: Social Practice and Inter-Religious Communication -- Experts, Border-Crossers and Cultural Brokers: The Knowledge of Islam and Contacts to Islamic Cultures at the Curia in the 15th Century -- Muslim Embassies in Renaissance Venice: The Framework of an Intercultural Dialogue -- Cultural Brokers in Relation with the Byzantine Court in the Later 14th and 15th Centuries -- The Vice-Chancellors of the Hospitallers on Rhodes -- Cultural Brokers at the Court of Lusignan Cyprus -- Jews, Christians and Muslims in the Middle Ages -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Mediterranean Region -- History -- 476-1517 -- Congresses; Mediterranean Region -- Religion -- Congresses; Aufsatzsammlung; Konferenzschrift -- 2010 -- Bochum; Kulturkontakt; Juden; Muslim; Christ; Hof; Mittelmeerraum